Homeroom Teacher's Action On Hyperactive Students Of MIN 3 West Aceh - Ade Kurniawan; Diyah Ismawati (Program Studi Pendidikan Agama Islam (PAI) Sekolah Tinggi Agama Islam Al Azhar, 2022)
This study aims to determine the behavioral tendencies of hyperactive students in State Islamic Elementary School 3 of West Aceh and how the homeroom teacher manages hyperactive students in MIN 3 West Aceh. This study employs a descriptive qualitative methodology. Observations, interviews, and documentation were employed as data gathering strategies. This investigation was carried out at State Islamic Elementary School 3 of West Aceh. This study involved one principal of State Islamic Elementary School 3 of West Aceh and two homeroom teachers who teach hyperactive students. Based on the study's findings, it is apparent that the hyperactive students of MIN 3 Aceh Barat exhibit motor and mixed hyperactivity with a combination type. The homeroom activities for dealing with hyperactive students consist of (1) arranging seats, (2) issuing warnings, (3) providing hyperactive students with guidance, and (4) building a madrasa setting appropriate to the growth of hyperactive students.